Understanding Arab Students’ Behavioral Patterns in an Online Course: An Explanatory Study Based on Hofstede’s National Cultural Dimensions - Ahmed Tlili (MDPI AG, 2021)
The provision of online learning experiences has been implemented by many universities worldwide to overcome several challenges, including inequality in education. However, this experience is still not a common approach in public universities in the Arab region. Furthermore, several research studies have pointed out that a country’s culture should be considered in order to enhance online learning, as students may behave differently based on their cultural backgrounds. Nevertheless, little is known about how a given culture may affect the learning behavioral patterns of students. Therefore, to better understand the cultural phenomenon and to enhance the adoption of online learning in the Arab region, this study aims to understand how an Arab culture may affect the online learning behaviors of students. Specifically, this study applies a lag sequential analysis (LSA) approach to understand the behavioral patterns of 116 students from Tunisia in a six-week online course. The study then further discusses the different learning behavior patterns based on the theoretical framework of Hofstede’s national cultural dimensions. The findings highlight that culture can affect how students engage in online learning discussions and how they maintain their learning performance online. The findings further indicate that online learning experiences may be beneficial for female students who experience social pressures in Arab cultures.